Illegal artisanal longline use in the Galapagos Marine Reserve characterized through monitoring and control data - Romero-Caicedo, Andres; Buitron-Lopez, Paola; Tapia-Jaramillo, Andres; McKinley, Simon J.; Castro-Briones, Edwin; Sevilla-Cedeño, Gonzalo; Ronquillo-Garzon, John; Maciel de Souza Vianna, Gabriel (Frontiers in Marine Science, 2025)
Illegal longline fishing in the Galapagos Marine Reserve (GMR) represents a socioecological issue with significant impact on protected marine species. This study characterizes the use of illegal longlines in the GMR by combining and analyzing datasets generated from monitoring and control operations by the Galapagos National Park Directorate. We explored temporal and spatial patterns of longline detections, identified impacted species, and estimated compliance of vessels associated with longlines. The number of longlines detected varied across years but no clear seasonal pattern was evident. The most frequently captured species taxa were sharks and rays, including critically endangered scalloped hammerheads (Sphyrna lewini) and endangered manta rays (Mobula birostris). The critically endangered waved albatrosses (Phoebastria irrorata), as well as green turtles (Chelonia mydas), were also captured. Longline fishing occurred frequently in the submarine canyon south of Isabela Island, the seamount east of Santa Cruz Island, and waters between Pinzon, Isabela, and Santiago Islands, which are areas of high primary productivity and popular fishing grounds. Longlines were also frequently recorded near Darwin and Wolf Islands, a regionally-important hotspot for shark conservation. Offending vessels associated with longlines represented 17% of the artisanal fleet targeting pelagic fish species and were responsible for approximately 30% of pelagic fish landings. Notably, 80% of the fishing trips by the offending vessels when longlines were recorded had no associated fisheries landing recorded. Offending vessels had their Automatic Identification Systems (AIS) deactivated, in 69% of the fishing trips when illegal longlines were recorded, despite their use being mandatory by law. These findings provide baseline data to assist managers of the GMR to improve enforcement effort allocation and underscore the importance of strengthening surveillance and enforcement efforts to mitigate illegal fishing activities.